2014
DOI: 10.1530/eje-13-0438
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of acromegalic patients exacerbated by concomitant type 2 diabetes requires higher pegvisomant doses to normalise IGF1 levels

Abstract: Objective: Acromegaly is associated with an increased prevalence of glucose metabolism disorders. Clinically confirmed diabetes mellitus is observed in approximately one quarter of all patients with acromegaly and is known to have a worse prognosis in these patients. Design: Of 514 acromegalic patients treated with pegvisomant and recorded in the German Cohort of ACROSTUDY, 147 had concomitant diabetes mellitus. We analysed these patients in an observational study and compared patients with and without concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 41 publications
2
22
1
3
Order By: Relevance
“…And in a study by Parkinson et al [21] in 118 acromegalic patients, gender, body weight, previous radiotherapy, and baseline GH/IGF-1 influenced the pegvisomant dosage that was needed to reach biochemical control. Additionally, the role of the diabetes status in the pegvisomant therapy scheme has been emphasized as patients with acromegaly and type 2 diabetes mellitus require higher pegvisomant dosages to achieve IGF-1 normalisation than acromegalic patients without diabetes mellitus [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…And in a study by Parkinson et al [21] in 118 acromegalic patients, gender, body weight, previous radiotherapy, and baseline GH/IGF-1 influenced the pegvisomant dosage that was needed to reach biochemical control. Additionally, the role of the diabetes status in the pegvisomant therapy scheme has been emphasized as patients with acromegaly and type 2 diabetes mellitus require higher pegvisomant dosages to achieve IGF-1 normalisation than acromegalic patients without diabetes mellitus [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…56,57 Diabetes mellitus is also associated with worse response to PEG therapy. 43,53 This has been observed in the German cohort of ACROSTUDY where IGF-I normalization rates were lower in diabetic patients (64%) than in non-diabetic ones (75%). Furthermore, the dose of PEG required for IGF-I normalization was higher in diabetic patients (18.9 mg/day) when compared to nondiabetic ones (15.5 mg/day).…”
Section: Determinants Of Peg Dosesmentioning
confidence: 74%
“…Additionally diabetic patients treated with insulin required higher PEG doses (22.8 mg/day) than those treated with oral hypoglycemic agents (17.2 mg/ day). 43 A possible explanation for these findings is the role of insulin as one of the main regulators of GHR liver expression. 58 In this regard, hyperinsulinemic diabetic patients (especially insulin treated cases) exhibit an increased expression of hepatic GHR, 59-61 thus requiring higher concentrations of PEG for full receptor blockage.…”
Section: Determinants Of Peg Dosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose requirements to achieve control of IGF-I seem to be higher in diabetic versus non-diabetic subjects [25]. A Spanish study reported that PEG-V showed an efficacy of >90%, but patients needed a dose escalation to maintain this high efficacy [13].…”
Section: Efficacy In Controlling Gh and Igf-imentioning
confidence: 99%